Survey of Insects that Attack Stored Bean Grains Vigna unguiculata (L.) and Phaseolus vulgaris L. in Porto Velho, Rondônia, Brazil - Silva, Thiarles Tezolim; Costa, Fábio Medeiros da (EntomoBrasilis, 2016)
Abstract. Beans are a staple component of human diet. However, grain storage for consumption is difficult due to pest attack. The objective of the present study was to conduct a survey of insects acting on the beans Phaseolus vulgaris L. and Vigna unguiculata (L.) in commercial stores in Porto Velho, Rondônia, Brazil. Samples were collected in small, medium-sized, and large markets. Percent infestation and weight loss caused by insects was evaluated during nine weeks. For V. unguiculata, 3.70% infestation was recorded from store PT 7 and the medium-sized market; the most serious situation occurred on the fifth week, when infestation reached 2.93%; weight loss was recorded from PT2 and PT7, with 19.19 g and 23.57 g. For P. vulgaris, infestation reached 3.70% in material from PT6; in small markets, infestation attained 0.84%; on the ninth week, 1.29% was recorded; weight loss from insects infestation occurred in samples from PT1 and PT6, 18.50 g and 9.78 g. Insect species found were Callosobruchus maculatus (Fabr.), Zabrotes subfasciatus (Boh.) and Acanthoscelides obtectus Say. Insect infestation did not significantly differ between both bean species. Levantamento dos Insetos que Atacam os Grãos de Feijão Armazenado Vigna unguiculata (L.) e Phaseolus vulgaris L.em Porto Velho, Rondônia, Brasil Resumo. O feijão é um componente fundamental na alimentação dos seres humanos. Entretanto, o armazenamento dos grãos para consumo se torna uma enorme dificuldade devido ao ataque de insetos. O presente estudo teve como objetivo realizar um levantamento de insetos que atacam feijão armazenado Phaseolus vulgaris L. e Vigna unguiculata (L.) em estabelecimentos comerciais de Porto Velho, Rondônia, Brasil. As amostras foram coletadas em mercados de pequeno, médio e grande porte, nas quais foi avaliado o percentual de infestação e perda de peso ocasionado pelos insetos durante nove semanas. Para V. unguiculata PT 7 registrou 3,70% de infestação, o mercado de médio porte atingiu 3,70%, a 5ª semana foi a mais agravante alcançando 2,93% de infestação, já a perda de peso ocorreu em PT2 e PT7 sendo 19,19 g e 23,57 g. Para P. vulgaris a infestação em PT6 chegou a 3,70% , em mercados de porte pequeno a infestação resultou em 0,84%, na 9ª semana observou-se 1,29%, em relação a perda de peso por infestação de insetos ocorreram em PT1 e PT6, sendo de 18,50 g e 9,78 g. As espécies de insetos encontradas foram Callosobruchus maculatus (Fabr.), Zabrotes subfasciatus (Boh.) e Acanthoscelides obtectus Say,em ambas as espécies de feijão não houve diferença significativa em relação as infestações pelas pragas.